Correlation of –160C > A and –347GA > G polymorphisms in E-cadherin gene and gastric cancer in north of Iran - Shekarriz, Ramin (J Res Med Sci, 2021)
BACKGROUND: E-cadherin (CDH1 gene) is a protein involved in cell-cell adhesion. There are reports on the association of –160C > A (rs16260) and –347GA > G (rs5030625) polymorphisms in the 5′-promoter region of the CDH1 gene with tumor development and progression of gastric cancer. This study aimed to examine the potential relationship between these two polymorphisms and gastric cancer in patients from Mazandaran province, Northern Iran. MATERIALS AND METHODS: A case–control study was conducted to test 97 patients and 95 healthy controls. Genomic DNA was extracted from peripheral blood followed by polymerase chain reaction amplification. Genotyping analysis was carried out using restriction fragment length polymorphism analysis for two potentially functional polymorphisms. RESULTS: Heterozygous genotype GA/G versus GA/GA of rs5030625 (–347 GA > G) was found to be associated with increased risk of gastric cancer in the people studied (odds ratio = 5.73, 95% confidence interval = 2.11–15.56, P = 0.001). Furthermore, AA or CA genotype in –160C > A polymorphism did not show any increased risk of gastric cancer (P = 0.559). CONCLUSION: The present study revealed that GA/G genotype of rs5030625 (–347 GA > G) polymorphism is associated with gastric cancer in Northern Iran.